PERDARAHAN INTRAKRANIAL PADA NEONATUS AKIBAT ACQUIRED PROTHROMBIN COMPLEX DEFICIENCY : Laporan Kasus - Ivytha; Yunus, Muhamad (CV. Jasa Sukses Abadi, 2024)
Acquired Prothrombin Complex Deficiency (APCD) is a state when blood coagulation cascade is disrupted due to lack of vitamin K levels in the body that often occurs in infants and neonates. APCD often manifest as a spontaneous intracranial bleeding among neonates which has given numbers to child morbidity and mortality rate globally. The main aim of this case report is to talks about a case of a baby girl age 1 month and 8 days whose referred to RSUD dr. H. Abdul Moeloek, Lampung Provence, with history of seizure and loss of consciousness. Physical examinoation has shown the anterior fontanels was tense, pale conjunctivas, and anisochor pupils with minimal light reflex. Blood works have shown lower Hb, longer PT and aPTT, other aspects within normal limits. Ultrasound of the fontanel and brain CT without contrast have shown intracranial bleeding. History of prophylactic vitamin K is unknown. After craniotomy procedure and few pharmacological treatment has given this patient gained clinical improvement. Laboratory findings in PT and aPTT also improved after intravenous vitamin K was administered for 3 consecutive days .